Argentinean Andean propolis associated with the medicinal plant Larrea nitida Cav. (Zygophyllaceae): HPLC-MS and GC-MS characterization and antifungal activity - Agüero, María Belén (2011)
The chemical profile and botanical origin of Andean Argentinian propolis were studied by HPLC-ESI-MS/MS and GC-MS techniques as well as the antifungal activity according to CLSI protocols. Dermatophytes and yeasts tested were strongly inhibited by propolis extracts (MICs between 31.25 and 125 μg/mL). The main antifungal compounds were: 3'methyl-nordihydroguaiaretic acid (MNDGA) 1, nordihydroguaiaretic acid (NDGA) 2 and a NDGA derivative 3, showing strong activity against Trichophyton mentagrophytes, T. rubrum and Microsporum gypseum (MICs between 15.6 and 31.25 μg/mL). The lignans 1 and 2 showed activities against clinical isolates of Candidas spp., Cryptococcus spp., T. rubrum and T. mentagrophytes (MICs and MFCs between 31.25 and 62.5 μg/mL). The lignan and volatile organic compounds (VOCs) profiles from propolis matched with those of exudates of Larrea nitida providing strong evidences on its botanical origin. These results support that Argentinian Andean propolis are a valuable natural product with potential to improve human health. Six compounds (1-6) were isolated from propolis for the first time, while compounds 1 and 3-6 were reported for first time as constituents of L. nitida Cav.